OP0212 DIGESTIVE INVOLVEMENT IN PATIENTS WITH PRIMARY SJÖGREN SYNDROME FROM THE SJOGRENSER SPANISH REGISTRY. (June 2019) - Melchor, Sheila; Sánchez-Piedra, Carlos; Castro, Monica Fernandez; Andreu, Jose Luis; Taboada, Victor Martinez; Olive, Alejandro; Rosas, Jose; Carreira, Patricia; ,
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease characterized by lymphocytic infiltration of the exocrine glands. Among the extraglandular manifestations, digestive involvement (DI) is frequent, and may condition the quality of life of these patients. There are few studies that systematically analyze gastrointestinal involvement in pSS. Objectives: To describe the prevalence of DI in patients with pSS included in SJOGRENSER Spanish registry and the phenotype of these patients, and to analyze their association with other clinical manifestations, serological markers, activity index and treatments used. Methods: Transversal multicenter study that includes all patients of SJOGRENSER registry (patients who meet 2002 pSS classification criteria), a study conducted in 33 units of rheumatology in Spain between 2014-2016, which collected demographic and clinical and serological data (1). Patients were classified according to the presence of DI (that included esophagus, stomach, intestine, liver and pancreas). A descriptive analysis was done, with means and standard deviations, frequencies and proportions. Student t for quantitative variables and Chi2 for qualitative ones were performed to evaluate differences between groups. The association of DI with other variables was analyzed by bivariate and multivariate binomial logistic regression analysis. In the multivariate model all variables with p <0.2 in the bivariate were included, and the effect of age and sex was controlled. Results: From 437 patients included (95% women, median age of 58 years), 59 (13.5%) had some DI (21 (36%) chronic atrophic gastritis, 12 (20%) esophageal dismotility, 3 (5%) lymphocytic colitis, 23 (39%) other). 54% of patients developed DI at the time of pSS diagnosis or later, and 45% before the diagnosis, with a mean age of 49 years at the onset of pSS symptoms. Patients with DI were older, both at diagnosis, onset of pSS symptoms and inclusion in the cohort, than those without it. There were no differences in the ESSDAI index between both groups. Comparison regarding clinical and serological characteristics is shown in Table 1. Patients with DI had more thyroid involvement and C3 hypocomplementemia. In addition, patients with DI had been treated more frequently with glucocorticoids and immunosuppressants. In the multivariate analysis, DI was significantly associated with older age at diagnosis (OR 1.03 (1.00-1.05); p=.005), more C3 hypocomplementemia (OR 2.40 (1.10-5.26) p=.027) and absence of anti-Ro antibodies (OR 0.33 (0.12-0.87) p=.025). Conclusion: In patients with pSS from the SJOGRENSER cohort, the prevalence of digestive involvement is 13.5%. These patients are older at diagnosis, have more C3 hypocomplementemia and negative anti-Ro antibodies. These patients need more frequently glucocorticoids and immunosuppressants, suggesting a more severe disease phenotype. Reference: [1] Fernandez Castro M, Reum Clin2016; 12:184-9 Disclosure of Interests: Sheila Melchor: None declared, Carlos Sánchez-Piedra: None declared, Monica Fernandez Castro: None declared, Jose Luis Andreu: None declared, Victor Martinez Taboada: None declared, Alejandro Olive: None declared, Jose Rosas Consultant for: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Speakers bureau: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Patricia Carreira: None declared